Incidence of Dengue Hemorrhagic Fever in the Selected Elementary Schools in Jolo and Its Preventive Measures Applied by Their School Prin-cipals, School Teachers, and School Nurses - Hayudini, Magna Anissa E. Aming; Hussin, Brenda E. Aming; Aming, Rofaida E.; Abdurahman, Jonrad Q.; Abdurahman, Arsheema E. Aming; Ynawat, Melchor B. (Future Science / FSH-PH Publications, 2022)
This study was purposely conducted to determine the preventive measures employed by the principals, teachers and school nurses in the elementary schools in Jolo and the incidence of dengue hemorrhagic fever was also investigated. Moreover, the significant difference between the employment of preventive measures and the incidence of dengue hemorrhagic fever were assessed. The descriptive method served as the research design of the study. In gathering data, a validated self-devised survey questionnaire was used and results were interpreted using the statistical tools of frequency, percentage, mean and chi-square. A focus group discussion was also conducted using interview guide questions tool, video recorded interviews and notes. The study revealed that majority of the preventive measures enumerated by the national agencies like Department of Health, Department of Science and Technology and Department of Education were implemented by the principals, teachers and school nurses among the selected elementary schools in Jolo. These included information dissemination about dengue hemorrhagic fever, observation of strict environmental sanitation, giving advice to pupils on the application of mosquito repellant and placement of Department of Science and Technology OVI-Larvicidal Tap inside the classroom at least once a week. The item on protection of pupils from mosquito bites showed that spraying of insecticides in classroom was poorly implemented. Unfortunately, results revealed that there was poor implementation on school children’s wearing of prescribed uniforms. As to the incidence of dengue hemorrhagic fever, there were 38 reported cases among children from the data provided from the Sulu Sanitarium and General Hospital and Sulu Provincial Hospital. The significant difference between the employment of preventive measures and the incidence of dengue hemorrhagic fever were revealed and the hypotheses were rejected.